2015
DOI: 10.1002/app.42095
|View full text |Cite
|
Sign up to set email alerts
|

UV curable soybean‐oil hybrid systems based on thiol‐acrylate and thiol‐ene‐acrylate chemistry

Abstract: In this study, epoxidized soybean oil was modified to prepare acrylated epoxidized soybean oil (AESO) and vinyl/acrylate ended soybean oil (VASO), which were blended with mercaptopropyl polyhedral oligomericsilsequioxane (POSS‐SH) to prepare UV curable thiol‐acrylate and thiol‐ene‐acrylate hybrid coatings. Photopolymerization processes of the coatings were measured and the results showed that addition of POSS‐SH obviously increased the conversion of double bond. The physical and mechanical properties of all cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Comparing with reported results [54][55][56][57] , the present three polymers show a little stronger hydrophilicity. This result is attributed to the fact that phosphorus is a high electronegative element and P=O bond has a strong tendency to form hydrogen bond with water.…”
Section: Surface Propertiessupporting
confidence: 75%
“…Comparing with reported results [54][55][56][57] , the present three polymers show a little stronger hydrophilicity. This result is attributed to the fact that phosphorus is a high electronegative element and P=O bond has a strong tendency to form hydrogen bond with water.…”
Section: Surface Propertiessupporting
confidence: 75%
“…Nevertheless, the obtained contact angle values are comparable to acrylated vegetable oil based photocured coatings. For instance, epoxidized soybean oil was reacted with acrylic acid and the coatings prepared therefrom exhibited a water CA of 75° . On the other hand, when methacrylated soybean oil was used in a photocurable composition at ~30%, the CA was found to be as 90° …”
Section: Resultsmentioning
confidence: 99%
“…Real‐time infrared technique is a useful and widely used method to monitor the curing profile of photocurable materials . The photopolymerization kinetics of the tung oil and ISTMP based coatings were monitored by following the change of the band intensity of the olefinic double bond at around 3010 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Acrylated epoxidized soybean oil was selected as the main monomer in this study because soybean oil is one of the most widely used vegetable oils in coatings and is considered an abundant and a low-cost feedstock (Sharma and Kundu, 2006). Moreover, acrylates are more reactive than epoxy-based monomers in UV curing (Malinauskas et al, 2013) and acrylated epoxidized soybean oil-based photocross-linked polymers showed promising properties for various applications (Kim et al, 2010;Liu et al, 2018;Miao et al, 2016;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%